Iron status in healthy subjects living in Jordan - Qatatsheh, Ala Ali; Dabbour, Ibrahim R.; Al-rethaia, Abdallah S.; Al-Holy, Murad A.; Omar, Sharaf S. (Progress in Nutrition, 2016)
Summary. Iron status was determined in 240 subjects who referred for routine check up in Zarqa governorate hospital located in Jordan. Prevalence of ferritin deficiency (